Novel Miniaturized Octaband Antenna for LTE Smart Handset Applications - Haixia Liu; Bo Lu; Long Li (International Journal of Antennas and Propagation)
A novel octaband LTE mobile phone antenna is presented, which has a compact size with the overall dimension of 35 mm × 9 mm × 3 mm. The miniaturized octaband antenna is implemented by a simple prototype of three parts which include a folded monopole as feeding element, main radiator element, and parasitic radiator element. The main and parasitic radiator elements are excited by the folded monopole feeding element coupling and shorting to the handset ground plane. A wide bandwidth in low-frequency bands covering from 747 MHz to 960 MHz (LTE Band13/GSM850/GSM900) is contributed by both main and parasitic radiator elements. In addition, the folded monopole is designed to resonate at 2530 MHz, and the coupling between the feeding element and main radiator element is designed to resonate at 1840 MHz. Subsequently, the wide bandwidth in high-frequency bands covering from 1710 MHz to 2690 MHz (DCS1800/PCS1900/WCDMA2100/LTE2300/LTE2500) is contributed by both structures. The antenna has the total efficiency up to 30% in low bands and up to 75% in high bands, respectively. At the same time, the proposed miniaturized octaband LTE mobile phone antenna is fabricated and tested to verify the design.